Accelerometer wear-site detection: When one site does not suit all, all of the time. Issue 4 (April 2017) - Rowlands, Alex V.; Olds, Tim S.; Bakrania, Kishan; Stanley, Rebecca M.; Parfitt, Gaynor; Eston, Roger G.; Yates, Thomas; Fraysse, François
Abstract: Objectives: Choice of accelerometer wear-site may facilitate greater compliance in research studies. We aimed to test whether a simple method could automatically discriminate whether an accelerometer was worn on the hip or wrist from free-living data. Design: Cross-sectional. Methods: Twenty-two 10–12 y old children wore a GENEActiv at the wrist and at the hip for 7-days. The angle between the forearm and the total acceleration vector for the wrist-worn monitor and between the pelvis and the total acceleration vector for the hip-worn monitor (i.e. the angle between the Y -axis component of the acceleration and the total acceleration vector) was calculated for each 5 s epoch. The standard deviation of this angle (SDangle) was calculated over time for the wrist-worn and hip-worn monitor for windows of varying lengths. We hypothesised that the wrist angle would be more variable than the hip angle. Results: Wear site could be discriminated based on SDangle; the shorter the time window the lower the optimal threshold and Area under the Receiver-Operating-Characteristic curve (AUROC) for discrimination of wear-site (AUROC = 0.833 (1 min) – 0.952 (12 h)). Classification accuracy was good for windows of 8 min (sensitivity = 90%, specificity = 87%, AUROC = 0.92) and plateaued for windows of ≥60 min (sensitivity and specificity >90%, AUROC = 0.95–0.96). Conclusions: We have presented a robust, computationally simple method that detects whether an accelerometer is being worn on the hip or wrist from 8 to 60 min of data. This facilitates the use of wear-site specific algorithms to analyse accelerometer data.